An Overview of Challenges Related to Power-Electronics Based Power Systems - Chavez-Orostica, H; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2021)
The Role of power electronics in the future of power system is becoming critical due to the growth in renewable energy generation and the evolution of technologies such as flexible alternating or direct current transmission systems. Consequently, electrical power systems are facing new challenges related to the reduction of inertia and increment of the requirements in terms of control and flexibility. In this context, this paper aims to facilitate future research in this subject by providing a compact overview of the main challenges of power electronic-based power systems, inertia management, stability and control issues. © 2021 IEEE.